Highly sensitive lateral flow immunoassays targeting PirA and PirB toxins for early on-site diagnosis of AHPND in shrimp - Chia-Chun Hsiao; You-Shan Cai; Shin-Yu Chou; Hung-Yun Lin; Shao-Chieh Yen; Han-Jia Lin; Shih-Chung Chang (Aquaculture, 2027)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Linking street-level greenery to environmental microbial diversity: A multiscalar analysis in the Taipei metropolitan area - Long Xie; Jussi Torkko; Marja Roslund; Tzen-Ying Ling; Juulia Manninen; Shih-Han Hung; Aki Sinkkonen; Tuula Jyske (Landscape and Urban Planning, 2026)

Process-oriented design of 3D-printed Fe–Co/biochar cathodes for mass-transfer-enhanced bioelectro-Fenton degradation of bisphenol A - Chi-Wen Lin; Shih-Hao Liu; Chung-Yen Yeh; Tzung-Han Chou; Shu-Hui Liu (Journal of Water Process Engineering, 2026)

A semi-implicit fully Eulerian WENO scheme for high-fidelity Vlasov–Ampère simulations - Mao-Syun Wong; Shih-Hung Chen; Tsung-Che Tsai; Kun-Han Lee (Computer Physics Communications, 2026)

Targeting Mitochondrial Dysfunction in Acute Organophosphate Toxicity: A Preliminary Evaluation of Cyclosporine A - David H. Jang; Jarelis Cabrera; Jonathan Starr; Abigail Insana; Angela N. Viaene; John C. Greenwood; Frances S. Shofer; Johannes K. Ehinger; Shih-Han Kao; Todd J. Kilbaugh (Journal of Medical Toxicology, 2026)
Background Organophosphate (OP) compounds are widely used agricultural chemicals that pose significant public health and chemical threat concerns due to their neurotoxic effects. Although OP toxicity has classically been attributed to acetylcholinesterase inhibition and cholinergic crisis, emerging evidence suggests mitochondrial dysfunction may represent an additional and clinically relevant mechanism of injury. Experimental OP exposure has been associated with impaired electron transport chain activity, reduced ATP production, increased oxidative stress, and disruption of mitochondrial membrane integrity. However, there are currently no established mitochondrial-targeted therapies for OP poisoning. Diisopropyl fluorophosphate (DFP), a well-established OP surrogate, reproduces several neurologic and mitochondrial features of nerve agent exposure. Cyclosporine A (CsA), an inhibitor of the mitochondrial permeability transition pore (mPTP), may represent a potential mitochondrial-targeted intervention. Methods This preliminary translational study employed both in vitro and in vivo models to evaluate mitochondrial respiratory dysfunction following acute DFP exposure and to explore the feasibility of mitochondrial-targeted treatment paradigms using CsA. Human donor-derived peripheral blood mononuclear cells (PBMCs) were used for DFP and CsA dose-finding and mitochondrial respiratory characterization using high-resolution respirometry (Oroboros O2k) with standardized substrate–uncoupler–inhibitor titration (SUIT) protocols. In parallel, a non-survivor Sprague–Dawley rat model of acute DFP exposure was developed incorporating invasive hemodynamic monitoring, controlled ventilation, venous blood gas analysis, and CsA treatment paradigms administered either following DFP exposure or as pretreatment prior to exposure. Brain cortical homogenates were prepared for ex vivo respiratory assessment. Results Preliminary findings demonstrated that DFP exposure was descriptively associated with impaired mitochondrial respiration across multiple oxidative phosphorylation (OXPHOS)- and electron transport system (ETS)-linked respiratory states in both PBMC and rodent models. DFP exposure was additionally associated with physiologic and metabolic derangements, including acidosis and elevated lactate concentrations. Post-DFP CsA administration was associated with partial preservation of mitochondrial respiration across several respiratory states, while the Pre-DFP CsA group demonstrated respiratory profiles more closely approximating control values in select OXPHOS- and ETS-linked states, accompanied by relatively preserved physiologic and metabolic parameters. Conclusions These preliminary findings support the feasibility of integrating mitochondrial respiratory phenotyping into translational models of acute OP toxicity and further support investigation of mitochondrial-targeted strategies in OP-associated mitochondrial dysfunction. The observed respiratory and physiologic trends associated with CsA exposure, particularly in the pretreatment paradigm, provide an exploratory foundation for future preclinical studies evaluating mitochondrial-directed countermeasures in OP poisoning.

Exploring genetic structure and habitat suitability of the masked palm civet (Paguma larvata) in Taiwan - Shih-Wei Chang; Tzong-Han Lin; Chi-Li Tsai; Hui-Yun Tseng (Mammalian Biology, 2026)

Typhoon driven joint extremes of wave height and wave period around Taiwan and implications for design sea states - Chun-Han Lo; Shih-Chun Hsiao (Ocean Engineering, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

New fossil moths (Lepidoptera: Micropterigidae) in middle Cretaceous Kachin amber from Myanmar - Ning Han; Xin-Ru Luo; Jia-Jia Wang; Chungkun Shih; Wei-Ting Zhang; Dong Ren (Palaeoworld, 2026)

S-scheme structure of novel 3D/2D lead-free perovskite/g-C3N4 photocatalyst for improved bisphenol A degradation under visible light - Ashkan Miri; Yonghao Xiao; Wei Xin Chan; Haoran Guan; Prashanth Venkatesan; Han Sen Soo; Yang-hsin Shih (Journal of Environmental Chemical Engineering, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Monitoring Strategy for Mudflat Wetlands: Selecting Indicator Species Based on Principal Component Analysis - Ta-Jen Chu; Yi-Qing Zhao; Yi-Jia Shih; Chun-Han Shih (Journal of Marine Science and Engineering, 2026)
Effective and cost-efficient monitoring is crucial in wetland management strategies. Large-scale surveys are time-consuming and uneconomical. Therefore, choosing between smaller-scale or alternative surveys is an important consideration in monitoring strategies. Indicator species (IS) are single species or a small number of target species that use specific characteristics as proxies or paradigms to represent community status or environmental indicators. To interpret and monitor changes caused by mangrove removal, we applied principal component analysis (PCA) and proposed a new concept to reveal the contribution of species to each principal component, thereby quantitatively identifying selectable ISs in environmental change. ISs were selected based on the total cumulative load of each species and the load of each species in each component. According to the load score algorithm in PCA, we identified five indicator species, namely, M. brevidactylus, M. banzai, U. arcuata, U. lacteal, and U. borealis. These ISs can clearly highlight changes during mangrove removal. PCA effectively reveals the relative changes of organisms across principal components by highlighting patterns and trends. It helps to detect environmental anomalies and assess their trends.

Economic and societal indicators in sustainable roadway rating systems – a comparative analysis - Shih-Hsien Yang; Nam Hoai Tran; Andrew S. Chang; Calista Y. Tsai; Han-Ruen Yueh (Environment, Development and Sustainability, 2026)

Chronic co-exposure to BPA and alcohol synergizes hepatotoxicity via dysregulation of glycerolipid metabolism and ceramide/HtrA2-driven apoptosis in HepG2 cells - Yan Qin Tan; Chia-Lung Shih; Yi-Chia Chen; Sheng-Han Lee; Ji-Rui Yang; Chan-Yen Kuo; Yi-Shiou Chiou (Journal of Hazardous Materials, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Multifunctional roles of WSSV079 and WSSV164 in RNA regulatory networks during WSSV replication in Litopenaeus vannamei - Brandon Rafael de Jesús Castillo-Corea; Shih-Shun Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Host acetyl-CoA pathways support WSSV replication - Shu-Wen Cheng; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Innovative analytical techniques for identifying metabolites of the UV filter homosalate through UPLC–MS: Environmental and health implications - Yi-Shiou Chiou; Chia-Hui Liu; Zih-Han Wu; Min-Feng Tseng; Shih-Chin Chang; Ya-Wen Chang; Chueh-Yi Huang; Chia-Lung Shih (Environmental Pollution, 2025)

Apply data science and feature selection techniques to predict carbon dioxide emissions in Taiwan - Shih-Hsien Tseng; Pei Han Feng; Thi Ha Trang Duong (Stochastic Environmental Research and Risk Assessment, 2025)

Corrigendum to “Assessing CO₂ sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050” [Mar. Pollut. Bull. 206 (2024) 116664]. - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santsch; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Prussian blue analog-derived Fe-Mn oxides for the enhanced activation of persulfate in sulfadiazine degradation: radical generation mechanism and electron transfer - Hao Meng; Yue Wang; Haiyan Yang; Jinglong Han; Dillirani Nagarajan; Shih-Hsin Ho; Jo-Shu Chang (Environmental Research, 2025)

Accelerating light-driven bioreaction with interfacial engineered microalgae-bacteria consortia: Unraveling positive charge-mediated biological interaction - Haixing Chang; Xueqing Gui; Meina Han; Jingwei Fu; Liandong Zhu; Shih-Hsin Ho (Chemical Engineering Journal, 2025)

Self-powered humidity sensor based on porous Ti₃C₂Tₓ MXene: High sensitivity and fast response for real-world applications - Linh Chi T. Cao; Luqman Hakim; Yuki Nagao; Sakoolkan Boonruang; Shih-Feng Tseng; Shu-Han Hsu (Chemical Engineering Journal, 2025)

Modified two-dose difference with stable isotope tracing workflow using mass shift defect filtering substantially reduces false positives in untargeted nifedipine metabolite profiling - Sheu-Fang Lo; Yi-Shiou Chiou; Jie-Huei Wang; Zih-Han Wu; Meng-Chi Yen; Chia-Lung Shih (Analytica Chimica Acta, 2025)

Enhancing physiological effects, subjective vitality, and emotional well-being through immersive experiences in biologically diverse environments - Shih-Han Hung; Tang-An Lee; A.-Young Lee; Chun-Yen Chang (Landscape and Ecological Engineering, 2025)

Toxicological assessment of inorganic arsenic: Bioaccumulation and immunotoxicity in Acanthopagrus schlegelii - Zhen-Hao Liao; Bo-Ying Chen; Han-Yang Yeh; Huai-Ting Huang; Shih-Lun Yuan; Po-Tsang Lee; Huu-The Nguyen; Yeh-Fang Hu; Fan-Hua Nan (Chemosphere, 2025)

Unveiling the hidden role of extracellular polymeric substances in microalgae-bacteria systems for enhanced electron transfer - Shengnan Li; Meina Han; Yun Bai; Yuhao Chu; Nan-Qi Ren; Shih-Hsin Ho (Chemical Engineering Journal, 2025)

Bile acid- and taurocholate-mediated virulence in AHPND-causing Vibrio parahaemolyticus is independent of the LuxO-OpaR quorum sensing cascade - Ramya Kumar; Shin-Jen Lin; Chien-Kang Huang; Shih-Shun Lin; Hao-Ching Wang; Fernand F. Fagutao; Han-Ching Wang (Aquaculture, 2025)

Layer-specific photo-metabolic specialization of encapsulated microalgae: A strategy for synchronous multi-nitrogen elimination from wastewater - Meina Han; Shengnan Li; Zhiling Li; Aijie Wang; Nanqi Ren; Shih-Hsin Ho (Water Research, 2025)

Sequential slot-die coating of perovskite solar cell modules under ambient conditions with precise phase-transition control - Chia-Feng Li; Shih-Han Huang; You-Ren Chen; Hou-Chin Cha; Ssu-Yung Chung; Yu-Hung Hsiao; Feng-Yu Tsai; Yu-Ching Huang (Chemical Engineering Journal, 2025)

Diluted swine and aquaculture wastewater enhance carbon sequestration and nutrient removal by the red seaweed Agardhiella subulata - W.Sanjaya Weerakkody; Hsueh-Han Hsieh; Vicente G Abedneko; Ka Hin Ling; Tzu-Chieh Chung; Zih-Yi Wang; Yung-Yen Shih; Tse-Min Lee; Chen Xu; Peter H. Santschi; Chin-Chang Hung (Bioresource Technology, 2025)

Blood Cells as a Cellular Biomarker for Mitochondrial Function in a Experimental Model of Acute Carbon Monoxide Poisoning with Treatment - Devesh Bungatavula; John C. Greenwood; Frances S. Shofer; Guthrie Buehler; Shih-Han Kao; Matthew Kelly; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2025)
Introduction Carbon monoxide (CO) is a leading cause of environmental poisoning in the United States with substantial mortality and morbidity. The mechanism of CO poisoning is complex and includes hypoxia, inflammation, and mitochondrial dysfunction. Currently both biomarkers and therapies for CO poisoning are limited and require new approaches. Methods Rats (~ 300 g) were divided into four groups of ten rodents per group (exposure): Control (room air), CO-400 (400 ppm), CO-1000 (1000 ppm) and CO-2000 (2000 ppm). Rodents received the assigned exposure through a secured tracheotomy tube over 120 min followed by 30 min of re-oxygenation at room air for a total of 150 min. Five additional rodents in each group were administered a succinate prodrug (NV354) at the start of exposure for the duration of the experiment until the reoxygenation period as separate experiments. Cortical brain tissue and whole blood were obtained for mitochondrial respiration. Stored plasma and snap frozen tissue stored at -80 o C were used to obtain protein quantification with Western Blotting. Results All animals in the Sham, CO-400, and CO-1000 groups survived until the end of the exposure period; no animals in the CO-2000 groups survived the exposure and were counted as attrition. We observed a dose-dependent decrease in key respiratory states in both isolated brain mitochondria and peripheral blood mononuclear cells (PBMCs), and, PBMCs respiration more positively correlated with isolated brain mitochondria when compared to carboxyhemoglobin (COHb). There was no significant difference in mitochondrial respiratory states in animals treated with NV354 compared to the untreated group. Conclusions The primary findings from this study include: (1) A dose-dependent decrease with key respiration states with higher concentrations of CO; (2) PBMCs had a higher correlation to isolated brain mitochondria respiration when compared to COHb; and (3) there was no treatment effect with the use of NV354.

Upcycling electroplating sludge into nanoflower-structured Cu-MOFs for efficient Fenton-like degradation of organic dyes - Jia-Yin Lin; Si-Han Yu; Jun-Ren Shih; Tsai-Hsuan Hsieh; Chih-Ying Wang; Jen-Yu Huang; Nai-Wen Tsao (Journal of Water Process Engineering, 2025)

Does perceived biophilic design contribute to human well-being in urban green spaces? A study of perceived naturalness, biodiversity, perceived restorativeness, and subjective vitality - Shih-Han Hung (Urban Forestry & Urban Greening, 2025)

Faceted-nanorods morphologies V2O5 nanostructures for enhanced CO2 photocatalytic conversion to CH4 under UV irradiation - Chih-Chiang Wang; An-Ya Lo; Yi-Jen Huang; Han-Chang Shih; Fuh-Shien Shieu; Tzu-Hsien Tseng; He-Ting Tsai (Journal of Environmental Chemical Engineering, 2025)

In vitro and in silico studies on α-glucosidase inhibitory properties of bioactive components from the rhizomes of Alpinia officinarum Hance - Zakhele Mphatsi Dlamini; Bongani Sicelo Dlamini; Shih-Han Fu; Ya-Lin Chang; Chi-Chien Lin; Yu-Kuo Chen; Kok-Tong Tan; Chi-I Chang (Medicinal Chemistry Research, 2025)

Typhoon Blend Wind Field Optimization Using Wave-Height Hindcasts - Tzu-Chieh Chen; Kai-Cheng Hu; Han-Lun Wu; Wei-Shiun Lu; Wei-Bo Chen; Wen-Son Chiang; Shih-Chun Hsiao (Journal of Marine Science and Engineering, 2025)
Typhoons cause significant losses and pose substantial threats every year, with an increasing trend observed in recent years. This study evaluates significant wave height (SWH) hindcasts for typhoons affecting Taiwan using optimized wind field configurations within the SCHISM-WWM-III coupled model. To enhance typhoon-induced SWH simulations, the blended wind field integrates ERA5 reanalysis wind data with the modified Rankine vortex wind model. Key parameters, including the parametric wind field start time, best track data, and the radius of maximum wind speed, were carefully selected based on analyses of typhoons Meranti and Megi in 2016. Validation metrics such as the skill core, HH indicator, maximum SWH difference, and peak time difference of the SWH indicate that the optimized setup improves the accuracy of simulation. The findings highlight the effectiveness of the adjusted blended wind field, the high-resolution best track data provided by Taiwan, and the maximum wind speed radius in significantly enhancing the accuracy of typhoon wave modeling for the waters surrounding Taiwan.

ARRDC3, a novel α-arrestin, modulates WSSV replication and AHPND pathogenesis in Litopeneaus vannamei - Ramya Kumar; Brandon Rafael de Jesús Castillo-Corea; Shih-Shun Lin; Chien-Kang Huang; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

The difference in roaming behavior between owned and unowned dogs in a satoyama landscape area - Tsung-Han Kuo; Gau-Ming Chang; Pin-Huan Yu; Wei-Hsuan Chen; Shih-Ching Yen (Applied Animal Behaviour Science, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

A comprehensive optimization of highly efficient MA-Free wide-bandgap perovskites for 4-T Perovskite/Silicon tandem solar cells - Yu-Ching Huang; Sheng-Wen Huang; Chia-Feng Li; Shih-Han Huang; Feng-Yu Tsai; Wei-Fang Su (Chemical Engineering Journal, 2025)

Integration of multiple observations for validation of mechanisms of earthquake-triggered groundwater level Anomalies: 2016 Taiwan Meinong earthquake - Shih-Jung Wang; Yan-Yao Lin; Ying-Han Chen; Chia-Lin Chung; Wen-Chi Lai; Chien-Chung Ke (Journal of Hydrology, 2024)

An Anisotropic Thermal–Mechanical Coupling Failure Criterion for Slate - Meng-Chia Weng; Shih-Shiang Lin; Chih-Shan Lee; Wei-Han Wu; Jia Han Li; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2024)
This study investigates the thermal–mechanical behavior of slates in geothermal reservoirs and establishes an anisotropic thermal–mechanical coupling failure criterion. Slate samples obtained from a geothermal site were subjected to a series of direct-shear and triaxial-compression tests at various confining pressures and temperatures. The results showed that the orientation angle within a specific range caused shear sliding failure of the slate, primarily due to foliation strength; beyond this range, intrinsic rock properties led to different failure modes. Elevated temperatures significantly diminished the strength anisotropy of the slate. These findings provided a foundation for the development of an anisotropic thermal–mechanical coupling failure criterion. The validity of the proposed criterion, which incorporates both the orientation angle and thermal degradation effects, was demonstrated through experimental results. A three-dimensional surface diagram was constructed to visualize the relationship between the temperature, orientation angle, and failure principal stress, highlighting the anisotropic thermal-degradation characteristics of the slate under varying confining pressures. This study enhances the understanding of the thermal–mechanical behavior of these materials in geothermal reservoirs.

Does built environment and natural leisure settings with bodies of water improve human psychological and physiological health? - Hsing-Fen Tang; A.-Young Lee; Shih-Han Hung (Landscape and Ecological Engineering, 2024)

Assessing the Role of Policy in the Evolution of Recreational Fisheries in Chinese Fishing Villages: An Analytical Hierarchy Process (AHP) and Delphi Method Analysis - Chun-Han Shih; Xin-Ruo Wang; Yu-Ming Lu; Ta-Jen Chu (Fishes, 2024)
Recreational fisheries in Chinese fishing villages have undergone significant transformation due to supportive government policies. This study develops a comprehensive indicator to objectively assess the development of recreational fisheries under rural revitalization policies. Six key dimensions were identified using the Analytical Hierarchy Process (AHP) and the Delphi method. The findings indicate that fishery resource conditions and environmental conditions are paramount, followed by service conditions, activities, policy conditions, and accommodation conditions. Key success indicators indicate the importance and priority of implementing policies, including “Tasting delicious aquatic products”, “Government support”, “Recreational fishing activities pricing”, and “Talent revitalization.” This study concludes by offering strategic recommendations to prioritize recreational fisheries within rural revitalization policies, utilizing identified indicators for policy implementation, and establishing a dedicated promotional group. These insights are essential for stakeholders and policymakers to promote sustainable and economically viable recreational fisheries in China.

Assessing CO2 sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050 - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santschi; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2024)

Insights into the removal of antibiotics from livestock and aquaculture wastewater by algae-bacteria symbiosis systems - Zhihua Xiao; Hao Meng; Shengnan Li; Weihao Ning; Youliang Song; Jinglong Han; Jo-Shu Chang; Yue Wang; Shih-Hsin Ho (Environmental Research, 2024)

Detachable acoustofluidic droplet-sorter - Dhrubajyoti Das; Shih-Hong Huang; Choa-Li Weng; Chien-Hung Yu; Chao-Kai Hsu; Yung-Chun Lee; Hui-Ching Cheng; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Finding harmony in the sea: Resolving conflicts by regional marine spatial planning - Jen-Han Yang; Yi Chang; Shih-Chun Hsiao (Ocean & Coastal Management, 2024)

Integrated multilevel investigation of photosynthesis revealed the algal response distinction to differentially charged nanoplastics - Saibo Liu; Jingheng Han; Linjie Yao; Huijun Li; Guorong Xin; Shih-Hsin Ho; Xiaochen Huang (Journal of Hazardous Materials, 2024)

Evaluating the anisotropic thermal–mechanical coupling strength of slate: A discrete element method approach - Minh-Triet Pham; Meng-Chia Weng; Hoang-Khanh Le; Shih-Shiang Lin; Wei-Han Wu (Computers and Geotechnics, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Comparative study of wave height transformation: Bragg reflection versus wave breaking at submerged rectangular breakwaters - Ching-Piao Tsai; Chun-Han Ko; Han-Chen Shih; Yueh-Heng Chen; Ying-Chi Chen (Ocean Engineering, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Cytoprotective alginate microcapsule serves as a shield for microalgal encapsulation defensing sulfamethoxazole threats and safeguarding nutrient recovery - Meina Han; Peng Xie; Nanqi Ren; Shih-Hsin Ho (Journal of Hazardous Materials, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

Isolation and characterization of the novel phage BP14 for lysing Vibrio parahaemolyticus and reducing virulence proteins - Te-Ken Hsu; Hui-Yu Shih; Hui-Ju Huang; Jeff Chia-Kai Hsu; Han-Ching Wang; Yi-Yin Chen; Li-Li Chen (Aquaculture, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Associations between paraben exposure, thyroid capacity, homeostasis and pituitary thyrotropic function in the general Taiwanese: Taiwan Environmental Survey for Toxicants (TEST) 2013 - Po-Chin Huang; Hsin-Chang Chen; Shih-Hao Leung; Yu-Jung Lin; Han-Bin Huang; Wan-Ting Chang; Hsin-I. Huang; Jung-Wei Chang (Environmental Science and Pollution Research, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Cell-Free DNA as a Biomarker in a Rodent Model of Chlorpyrifos Poisoning Causing Mitochondrial Dysfunction - Shih-Han Kao; Frances S. Shofer; John C. Greenwood; Oladunni Alomaja; Abhay Ranganathan; Sarah Piel; Clementina Mesaros; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

Indolocarbazole-based small molecules as guest donors for High-Performance ternary organic photovoltaics - Hsiao Han Chiu; Bing-Huang Jiang; Hong Chi Wang; Xuan-Ming Su; Yu-Hsuan Kang; Yu-Wei Su; Hui-Shan Shih; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2023)

Corrigendum to “Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions” [Sci. Total Environ. 855 (2023) 158850] - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Assessment of various conditions for the simultaneous determination of US EPA and EU priority PAHs in coffee samples and their PAHs consumption risk - Yu-Fang Huang; Po-Lin Liao; Yi-Jun Lin; Shih-Han Huang; Yi-Hsieng Samuel Wu; Chia-Fang Teng; Deng-Jye Yang (Food Research International, 2023)

Volunteering in nature: a win–win strategy for healthy people and healthy nature - Wan-Yu Chou; Shih-Han Hung; Chun-Yen Chang; Tsu-Liang Chang (Landscape and Ecological Engineering, 2023)

Onsite restorative effect of a rural ecological farm versus an urban public greenery space - Yu-Hsin Tung; Shih-Han Hung; Chun-Yen Chang; Hsing-Fen Tang (Landscape and Ecological Engineering, 2023)

Involvement of microRNA164 in responses to heat stress in Arabidopsis - Wei-An Tsai; Po-Han Sung; Yun-Wei Kuo; Ming-Cheng Chen; Shih-Tong Jeng; Jeng-Shane Lin (Plant Science, 2023)

Algae-mediated bioremediation of ciprofloxacin through a symbiotic microalgae-bacteria consortium - Yue Wang; Weihao Ning; Meina Han; Changfei Gao; Wanqian Guo; Jo-Shu Chang; Shih-Hsin Ho (Algal Research, 2023)

Study of the Optimal Grid Resolution and Effect of Wave–Wave Interaction during Simulation of Extreme Waves Induced by Three Ensuing Typhoons - Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen (Journal of Marine Science and Engineering, 2023)
Three typhoons, Meranti, Malakas, and Megi, occurred successively in eastern Taiwanese waters in September 2016, causing extreme waves (significant wave height > 10.0 m), and these events were selected to investigate the effect of model grid resolution and wave–wave interaction on simulating typhoon-driven waves. The WAVEWATCH III (WW3) model, with 0.50 deg, 0.25 deg, 0.20 deg, 0.10 deg, and 0.05 deg grid resolutions, and two reanalysis wind fields were adopted to simulate ocean waves during these three typhoons. The results indicated that the exertion of the Climate Forecast System version 2 (CFSv2) winds over the WW3 model with 0.10 deg grid resolution yielded optimum simulations of typhoon waves in a compromise between accuracy and elapsed time. In the present study, the WW3 model modeled nonlinear wave–wave interactions using discrete interaction approximation (DIA). The numerical experiments revealed that the underestimations of typhoon waves were significant when the WW3 model excluded nonlinear wave–wave interactions, especially when employing a higher grid resolution. This study also found that the WW3 model is superior to the Wind Wave Model III (WWM-III) using the CFSv2 winds because the WWM-III tended to overestimate the extreme waves in all three of these eastern Taiwan typhoon events that occurred in September 2016.

Alteration in Cerebral Metabolism in a Rodent Model of Acute Sub-lethal Cyanide Poisoning - Oladunni Alomaja; Frances S. Shofer; John C. Greenwood; Sarah Piel; Carly Clayman; Clementina Mesaros; Shih-Han Kao; Samuel S. Shin; Johannes K. Ehinger; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2023)

Seasonal variations, source apportionment and dry deposition of chemical species of total suspended particulate in Pengjia Yu Island, East China Sea - Li Yu-Xiao; Liu Shu-Han; Luo Li; Yang Shu-Di; Lu Bin-Yu; Wang Chen; Hsu Shih-Chieh; Kao Shuh-Ji (Marine Pollution Bulletin, 2023)

Carbon capture by macroalgae Sarcodia suae using aquaculture wastewater and solar energy for cooling in subtropical regions - W. Sanjaya Weerakkody; Ka Hin Ling; Hsueh-Han Hsieh; Vicente G. Abedneko; Jeng-Feng Shyu; Tse-Min Lee; Yung-Yen Shih; R.R.M.K.P. Ranatunga; Peter H. Santschi; Chin-Chang Hung (Science of The Total Environment, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Genetic Variations and Expansion of the Blue Swimmer Crab (Portunus pelagicus) in Southeast Asia - Yu-Ming Lu; Chun-Han Shih; Po-Cheng Chen; Wei-Chieh Kao; Ying-Chou Lee; Yu-San Han; Tzong-Der Tzeng (Journal of Marine Science and Engineering, 2022)
Blue swimmer crabs (Portunus pelagicus) primarily inhabit the coastal regions of Southeast Asia. This study aimed to examine their population genetic structure, phylogeography, and historical demography by applying partial sequences to the control region in the mitochondrial DNA. The analysis focused on 6 populations comprising 166 individual samples collected from Taiwan (Kezailiao Kaohsiung (KK) and Penghu (PH)), mainland China (Xiamen (XM) and Hong Kong (HK)), Vietnam (Hanoi (VN)), and Singapore (SGP). The estimated nucleotide diversity (π) for all of the samples was 0.062, with values ranging between 0.018 (PH) and 0.045 (HK). Our study collected 116 haplotypes and classified them into lineages A and B. The XM, HK, VN, and SGP populations made up lineage A, and the PH and KK populations comprised lineage B. For each lineage, the results highlighted indications of demographic expansion. Lineage A can be traced back to the second-to-last interglacial period, while lineage B possibly originated in the last glacial period. There were significant differences in the FST values among the six populations, except for the pairs HK–XM and PH–KK. In conclusion, the phylogeography and genetic structure of P. pelagicus in Southeast Asia were potentially affected by the Pleistocene glacial cycles and human introduction. These findings further highlight the possible dispersal routes of P. pelagicus throughout Southeast Asia.

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Evaluation of PET List Data-Driven Gated Motion Correction Technique Applied in Lung Tumors - Yi-Lun Chen; Bang-Hung Yang; I.-Ling Shih; Ko-Han Lin (Journal of Medical and Biological Engineering, 2022)

Energy performance of European countries by considering the role of forest - Liang Chun Lu; Shih-Yung Chiu; Yung-Ho Chiu; Tzu-Han Chang; William Tang (Environmental Science and Pollution Research, 2022)

Do Forests help environmental development of Cities in China? - Liang Chun Lu; Yung-ho Chiu; Shih-Yung Chiu; Tzu-Han Chang (Environment, Development and Sustainability, 2022)

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Phylogeography and Genetic Structure of the Swimming Crabs Portunus sanguinolentus (Herbst, 1783) in East Asia - Yu-Ming Lu; Chun-Han Shih; Po-Cheng Chen; Wei-Chieh Kao; Ying-Chou Lee; Yu-San Han; Tzong-Der Tzeng (Journal of Marine Science and Engineering, 2022)
The three-spot swimming crab (Portunus sanguinolentus) is mainly distributed in South East Asia. An analysis of mitochondrial control region partial sequences allows us to determine the population genetic structure, phylogeography and historical demography of this species in East Asia. The seven populations, which included 110 individuals, were collected from mainland China (Shanghai, SH, Xiamen, XM and Hong Kong, HK), Taiwan (Yilan, YL, Taichung, TC, Donggang, DG) and Singapore (Singapore, SGP). The nucleotide diversity (π) of all individuals was 0.01149, with values ranging from 0.00372 (SGP) to 0.01345 (YL). In total, 90 haplotypes have been identified, which can be divided into two major lineages: lineage A consists of specimens from SH, YL, XM, TC and DG, and lineage B corresponds to specimen from SGP. From the second to the most recent interglacial period, population expansion was observed in each lineage. However, a low level of genetic differentiation was also observed in the three-spotted swimming crab, P. sanguinolentus, according to FST values. Our results suggest that several past and present habitat configurations have shaped the genetic patterns of P. sanguinolentus until now. During Pleistocene glaciations, when sea levels were low, this species may have moved along the coast from Southeast Asia to China. It first colonized the Hong Kong area during this era. After sea levels rose and shorelines receded, it subsequently spread to the coast of mainland China.

Evaluating the Effects Related to Restocking and Stock Replenishment of Penaeus penicillatus in the Xiamen Bay, China - Jia-Qiao Wang; Yi-Jia Shih; Liang-Ming Huang; Jun Li; Wei-Wen Li; Chun-Han Shih; Ta-Jen Chu (Journal of Marine Science and Engineering, 2021)
The quantitative evaluation of restocking and stock replenishment is essential for providing operational feedback and implementing adaptive management for future restoration projects. Since 2010, approximately 700 million juvenile shrimp (Penaeus penicillatus) have been released into Xiamen Bay, Fujian Province, China, each year, through stock replenishment programs. The recruited shrimp were sampled through three-year bottom trawl surveys from 2014 to 2017. The biological characteristics and catch equation were used to evaluate the effect of restocking and stock replenishment. The analysis uses the FAO-ICLARM Stock Assessment Tool (FISAT II) program. In general, there are two sources of recruitments—one from spawning brood stock and the other from released juvenile shrimp. We constructed an evaluation model for an effect evaluation based on Baranov’s catch equation to separate the initial recruitment volume using survey data. The relationship between body weight and total length was W = 1.638 TL2.9307. There is no statistically significant difference between males and females. The von Bertalanffy growth parameters derived for prawns, using FiSAT II, were L∞ = 209.6 mm and K = 0.51 per year. In spring 2014, the initial resource amount was 49,200, while the ratio of effective recruitment and parent amount was 3.92. The survival rate of the released shrimp larvae, 1.88‱, seems to be very unsatisfactory. The resource amount in summer and autumn is higher than in winter and spring. Obviously, the restocking effect is lower and the programs need to be improved. To improve the restocking effect, the replenishment performance should be adjusted to reduce the mortality rate and increase its release effectiveness. Therefore, corresponding implementations are recommended, including standard extensive culture, reduction in stress during transportation, and temporary culture.

Numerical Analysis of the Effect of Binary Typhoons on Ocean Surface Waves in Waters Surrounding Taiwan - Tzu-Yin Chang; Hongey Chen; Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen (Frontiers in Marine Science, 2021)
The ocean surface waves during Super Typhoons Maria (2018), Lekima (2019), and Meranti (2016) were reproduced using hybrid typhoon winds and a fully coupled wave-tide-circulation modeling system (SCHISM-WWM-III). The hindcasted significant wave heights are in good agreement with the along-track significant wave heights measured by the altimeters aboard the SARAL (Satellite with ARgos and ALtiKa) and Jason-2 satellites. Two numerical experiments pairing Super Typhoons Maria (2018) and Meranti (2016) and Super Typhoons Lekima (2019) and Meranti (2016) were conducted to analyze the storm wave characteristics of binary and individual typhoons. Four points located near the tracks of the three super typhoons were selected to elucidate the effects of binary typhoons on ocean surface waves. The comparisons indicate that binary typhoons not only cause an increase in the significant wave height simulations at four selected pints but also result in increases in the one-dimensional wave energy and two-dimensional directional wave spectra. Our results also reveal that the effects of binary typhoons on ocean surface waves are more significant at the periphery of the typhoon than near the center of the typhoon. The interactions between waves generated by Super Typhoons Maria (2018) and Meranti (2016) or Super Typhoons Lekima (2019) and Meranti (2016) might be diminished by Taiwan Island even if the separation distance between two typhoons is <700 km.

Incorporating Species-Conditional Co-Occurrence When Selecting Indicator Species to Monitor Restoration after Mangrove Removal from the Siangshan Wetland, Taiwan - Ta-Jen Chu; Chun-Han Shih; Yu-Ming Lu; Yi-Jia Shih; Jia-Qiao Wang; Liang-Ming Huang (Journal of Marine Science and Engineering, 2021)
This paper presents an approach for incorporating species-conditional co-occurrence into models used for the selection of marine indicator species. Mangrove invasion within the Siangshan Wetland in Hsinchu, Taiwan, has changed the original structures and functions of habitats for benthic organisms. The Hsinchu City Government ran a large-scale mangrove removal project from October 2015 to March 2016 to restore the wetland. From October 2015 to September 2016, we investigated the biological effects of mangrove removal on benthic crabs and their adjacent habitats. Density, number of species, Shannon–Weaver index (H′) and Palou’s evenness index (J′) were calculated and compared between mangrove and non-mangrove regions. The results showed that values for these attributes in the non-mangrove regions were higher than those of the mangrove regions. After mangrove removal, species returned to their original habitats and the related density increased significantly. Using conditional co-occurrence algorithms, we identified five indicator species (Mictyris brevidactylus, Macrophthalmus banzai, Uca arcuata, Uca lacteal and Uca borealis) with high co-occurrence probabilities, whose population responses provided direct evidence of the benefits of mangrove removal for wetland restoration. The results indicate that mangrove removal is an appropriate habitat rehabilitation strategy for benthic organisms, and that the chosen indicator species may provide valuable ecological information for coastal managers seeking to control the spread of mangroves.

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Nanotechnology advances in pathogen- and host-targeted antiviral delivery: multipronged therapeutic intervention for pandemic control - Kai-Chieh Yang; Jung-Chen Lin; Hsiao-Han Tsai; Chung-Yao Hsu; Vicky Shih; Che-Ming Jack Hu (Drug Delivery and Translational Research, 2021)

Effect of Depth-Induced Breaking on Wind Wave Simulations in Shallow Nearshore Waters off Northern Taiwan during the Passage of Two Super Typhoons - Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen; Wen-Dar Guo; Chih-Hsin Chang; Wen-Ray Su (Journal of Marine Science and Engineering, 2021)
Super Typhoons Maria (2018) and Lekima (2019) were adopted for this case study, although they only passed the northern offshore waters of Taiwan without making landfall. A direct modification technique was employed to create the atmospheric conditions for a wave-circulation model to hindcast large typhoon-driven waves. The radius of the modified scale (Rtrs) for a hybrid typhoon wind plays an important role in the significant wave height (SWH) simulations during the passage of typhoons. The maximum increment in peak SWH reached 3.0 m and 5.0 m in the deep ocean for Super Typhoons Maria (2018) and Lekima (2019), respectively if the Rtrs was increased from 4 × Rmax (radius of the maximum wind) to 7 × Rmax. The SWHs induced by the typhoon winds in the surf zone were more sensitive to different wave-breaking formulations used in the wave-circulation model. The maximum difference in peak SWH reached 2.5 m and 1.2 m for Super Typhoons Maria (2018) and Lekima (2019), respectively, when the wave-breaking formulations of BJ78 (proposed by Battjes and Janssen in 1978) and CT93 (proposed by Church and Thornton in 1993) were introduced to the wave-circulation model. The SWH simulations in the surf zone were insensitive to the wave-breaking criterion (γ) during the passage of typhoons. In shallow nearshore waters, the utilization of a constant γ for the wave-circulation model always produces peak SWHs that are smaller than those using γ based on local steepness or peak steepness.

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Timing of coseismic displacement grid model construction for updating the semi-kinematic reference frame: case study in Taiwan - Shih-Han Hsiao; Kuo-En Ching; Kwo-Hwa Chen; Chien-Kuan Li (Journal of Geodesy, 2021)

Dapagliflozin suppresses ER stress and protects doxorubicin-induced cardiotoxicity in breast cancer patients - Wei-Ting Chang; Yu-Wen Lin; Chung-Han Ho; Zhih-Cherng Chen; Ping-Yen Liu; Jhih-Yuan Shih (Archives of Toxicology, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

On the Sensitivity of Typhoon Wave Simulations to Tidal Elevation and Current - Shih-Chun Hsiao; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
The sensitivity of storm wave simulations to storm tides and tidal currents was investigated using a high-resolution, unstructured-grid, coupled circulation-wave model (Semi-implicit Cross-scale Hydroscience Integrated System Model Wind Wave Model version III (SCHISM-WWM-III)) driven by two typhoon events (Typhoons Soudelor and Megi) impacting the northeastern coast of Taiwan. Hourly wind fields were acquired from a fifth-generation global atmospheric reanalysis (ERA5) and were used as meteorological conditions for the circulation-wave model after direct modification (MERA5). The large typhoon-induced waves derived from SCHISM-WWM-III were significantly improved with the MERA5 winds, and the peak wave height was increased by 1.0–2.0 m. A series of numerical experiments were conducted with SCHISM-WWM-II and MERA5 to explore the responses of typhoon wave simulations to tidal elevation and current. The results demonstrate that the simulated significant wave height, mean wave period and wave direction for a wave buoy in the outer region of the typhoon are more sensitive to the tidal current but less sensitive to the tidal elevation than those for a wave buoy moored in the inner region of the typhoon. This study suggests that the inclusion of the tidal current and elevation could be more important for typhoon wave modeling in sea areas with larger tidal ranges and higher tidal currents. Additionally, the suitable modification of the typhoon winds from a global atmospheric reanalysis is necessary for the accurate simulation of storm waves over the entire region of a typhoon.

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Description of Gemmobacter aestuarii sp. nov., isolated from estuarine surface water and reclassification of Cereibacter changlensis as Gemmobacter changlensis Chen et al. 2013 - Asif Hameed; Mariyam Shahina; Shih-Yao Lin; Wen-Ming Chen; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Archives of Microbiology, 2020)

Description of Azoarcus nasutitermitis sp. nov. and Azoarcus rhizosphaerae sp. nov., two nitrogen-fixing species isolated from termite nest and rhizosphere of Ficus religiosa - Shih-Yao Lin; Asif Hameed; Chia-Fang Tsai; Guan-Hua Huang; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2020)

Effects of Hyperbaric Oxygen Therapy on Acute Myocardial Infarction Following Carbon Monoxide Poisoning - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Chien-Chin Hsu; Hung-Jung Lin; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2020)

Numerical Simulation of Large Wave Heights from Super Typhoon Nepartak (2016) in the Eastern Waters of Taiwan - Shih-Chun Hsiao; Hongey Chen; Han-Lun Wu; Wei-Bo Chen; Chih-Hsin Chang; Wen-Dar Guo; Yung-Ming Chen; Lee-Yaw Lin (Journal of Marine Science and Engineering, 2020)
Super Typhoon Nepartak (2016) was used for this case study because it is the most intense typhoon that made landfall in Taiwan in the past decade. Winds extracted from the Climate Forecast System version 2 (CFSV2) and ERA5 datasets and merged with a parametric typhoon model using two hybrid techniques served as the meteorological conditions for driving a coupled wave-circulation model. The computed significant wave heights were compared with the observations recorded at three wave buoys in the eastern waters of Taiwan. Model performance in terms of significant wave height was also investigated by employing the CFSV2 winds under varying spatial and temporal resolutions. The results of the numerical experiments reveal that the simulated storm wave heights tended to decrease significantly due to the lower spatial resolution of the hourly winds from the CFSV2 dataset; however, the variations in the storm wave height simulations were less sensitive to the temporal resolution of the wind field. Introducing the combination of the CFSV2 and the parametric typhoon winds greatly improved the storm wave simulations, and similar phenomena can be found in the exploitation of the ERA5 dataset blended into the parametric wind field. The overall performance of the hybrid winds derived from ERA5 was better than that from the CFSV2, especially in the outer region of Super Typhoon Nepartak (2016).

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Design and functions of floating architecture – a review - Yuan-Ho Lin; Yung Chih Lin; Han-Shih Tan (Marine Georesources & Geotechnology, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

The effect of caffeine on cerebral metabolism during alpha-chloralose anesthesia differs from isoflurane anesthesia in the rat brain - Shin-Lei Peng; Han Chiu; Chun-Yi Wu; Chiun-Wei Huang; Yi-Hsiu Chung; Cheng-Ting Shih; Wu-Chung Shen (Psychopharmacology, 2019)

Risk of Myocardial Infarction After Carbon Monoxide Poisoning: A Nationwide Population-Based Cohort Study - Chien-Cheng Huang; Chung-Han Ho; Yi-Chen Chen; Hung-Jung Lin; Chien-Chin Hsu; Jhi-Joung Wang; Shih-Bin Su; How-Ran Guo (Cardiovascular Toxicology, 2019)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

First molecular detection of Anaplasma phagocytophilum in the hard tick Rhipicephalus haemaphysaloides in Taiwan - Chi-Chien Kuo; Jing-Lun Huang; Chia-Hao Chien; Han-Chun Shih; Hsi-Chieh Wang (Experimental and Applied Acarology, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Estimating the Ungauged Natural Flow Regimes for Environmental Flow Management - Han-Chung Yang; Jian-Ping Suen; Shih-Kai Chou (Water Resources Management, 2016)

Regulation of allergic inflammation by the ectoenzyme E-NPP3 (CD203c) on basophils and mast cells - Shih Han Tsai; Kiyoshi Takeda (Seminars in Immunopathology, 2016)

Validation of cross-contamination control in biological safety cabinet for biotech/pharmaceutical manufacturing process - Shih-Cheng Hu; Angus Shiue; Jin-Xin Tu; Han-Yang Liu; Rong-Ben Chiu (Environmental Science and Pollution Research, 2015)

Analysis and Potential Alternatives for the Disputed South China Sea from Ocean Governance in the Polar Regions - Ray Tsung-Han Tai; Nathaniel S. Pearre; Shih-Ming Kao (Coastal Management, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Lysobacter lycopersici sp. nov., isolated from tomato plant Solanum lycopersicum - Shih-Yao Lin; Asif Hameed; Cheng-Zhe Wen; You-Cheng Liu; Yi-Han Hsu; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Description of Algoriphagus taiwanensis sp. nov., a xylanolytic bacterium isolated from surface seawater, and emended descriptions of Algoriphagus mannitolivorans, Algoriphagus olei, Algoriphagus aquatilis and Algoriphagus ratkowskyi - Mariyam Shahina; Asif Hameed; Shih-Yao Lin; Wei-An Lai; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Description of Niveispirillum fermenti gen. nov., sp. nov., isolated from a fermentor in Taiwan, transfer of Azospirillum irakense (1989) as Niveispirillum irakense comb. nov., and reclassification of Azospirillum amazonense (1983) as Nitrospirillum amazonense gen. nov - Shih-Yao Lin; Asif Hameed; Fo-Ting Shen; You-Cheng Liu; Yi-Han Hsu; Mariyam Shahina; Wei-An Lai; Chiu-Chung Young (Antonie van Leeuwenhoek, 2014)

Identification and characterization of the microRNA transcriptome of a moth orchid Phalaenopsis aphrodite - Ya-Ting Chao; Chun-Lin Su; Wen-Han Jean; Wan-Chieh Chen; Yao-Chien Alex Chang; Ming-Che Shih (Plant Molecular Biology, 2014)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Effect of particle size of titanium dioxide nanoparticle aggregates on the degradation of one azo dye - Yang-hsin Shih; Cheng-han Lin (Environmental Science and Pollution Research, 2012)

Using differential SAR interferometry to map land subsidence: a case study in the Pingtung Plain of SW Taiwan - Chia-Sheng Hsieh; Tian-Yuan Shih; Jyr-Ching Hu; Hsin Tung; Mong-Han Huang; Jacques Angelier (Natural Hazards, 2011)

Orchestrating T-cell receptor α gene assembly through changes in chromatin structure and organization - Han-Yu Shih; Bingtao Hao; Michael S. Krangel (Immunologic Research, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Characteristic Study of Dry Deposition, Concentration, Compositions for Particulates Mass and Ionic Species During Summer and Autumn Season at a Traffic Sampling Site - Guor-Cheng Fang; Yuh-Shen Wu; Jui-Yeh Rau; Shih-Han Huang (Environmental Monitoring and Assessment, 2006)